Underlying anti-hypertensive mechanism of the Mizuhopecten yessoensis derived peptide NCW in spontaneously hypertensive rats via widely targeted kidney metabolomics - Wenjun Xue; Wenzhu Zhao; Sijia Wu; Zhipeng Yu (Food Science and Human Wellness)
The angiotensin-converting enzyme (ACE) inhibitory peptide NCW derived from Mizuhopecten yessoensis has been demonstrated to have significant in vivo anti-hypertensive effects, however, its anti-hypertensive mechanism is still not fully clarified. This study established a UPLC-Q-TRAP-MS/MS-based widely targeted kidney metabolomics approach to explore the changes of kidney metabolic profiles and to clarify the anti-hypertensive mechanism of peptide NCW in spontaneously hypertensive rats (SHRs). Multivariate statistical analysis indicated that the kidney metabolic profiles were clearly separated between the SHR-NCW and SHR-Untreated groups. A total of 85 metabolites were differentially regulated, and 16 metabolites were identified as potential kidney biomarkers, e.g., 3-hydroxybutyrate, malonic acid, deoxycytidine, and L-aspartic acid. The peptide NCW might regulate kidney metabolic disorder of SHRs to alleviate hypertension by suppressing inflammation and improving nitric oxide production under the regulation of linoleic acid metabolism, folate related pathways, synthesis and degradation of ketone bodies, pyrimidine metabolism, β-alanine metabolism, and retinal metabolism.